Phonology-based reading instruction to improve dyslexic students’ early reading ability - Novianti, Ranti; Syihabuddin, S.; Rochyadi, Endang (Universitas Pendidikan Indonesia, 2019)
Dyslexic students struggle to learn how to read. Yet, few studies reported on how dyslexic students learn to read. In this respect, special education teachers have adopted a myriad of ways to overcome dyslexic students’ reading problems. To respond to this need, the purpose of this study is to examine how phonology-based reading instruction could help dyslexic students improve their early reading abilities. Grounded in a mixed methods research design, four dyslexic students of primary school were recruited to participate in this study. The results of the study showed that the phonology-based reading instruction had a positive impact on improving the dyslexic students’ early reading abilities, particularly in Bahasa Indonesian-medium reading texts. This suggests that phonology-based reading instruction could effectively be implemented if special education teachers could enact phonological instruction as a prerequisite for identifying the students’ early reading ability and phonics instruction as an instructional reinforcement for building students’ early reading repertoire.